(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2024)
The dissolution of the Soviet Union (USSR), culminating on December 25, 1991, had significant consequences for the former Soviet republics and the global geopolitical landscape. Following the collapse, complex processes of systemic unraveling emerged as a result of this pivotal moment. Conflict between Ukraine and Russia, particularly the annexation of Crimea, triggered profound changes in the Ukrainian economy. The loss of control over Crimea led to a reduction in resources and potential revenues that traditionally contributed to the Ukrainian economy. The region of Crimea, characterized by diverse ethnic and cultural identities, including the Crimean Tatar population, became a focal point in discussions about preserving diversity and integration within Ukraine’s borders. Despite fundamental arguments regarding the significance of Crimea for both Russia and Ukraine, the interpretation and value of this territory vary depending on political, historical, and national perspectives. In recent years, Crimea has become the epicenter of complex geopolitical conflicts and rivalries between Russia and Ukraine, while the territorial belonging of the region remains a contentious issue.